The Mindset of Christ As The Foundation of The Church in Building Religious Harmony: An Interpretation of Philippians 2: 5 - Daido Tri Sampurna Lumbanraja (Jurnal Dialog, 2021)
Building religious harmony is the duty and responsibility of all Indonesian people. Church is an essential part of Indonesian society which is also obliged to develop religious harmony. Answering the question of how the church should behave and act in a pluralistic society is to offer the teaching concept of the mindset of Christ. As it is contained in Philippians 2: 5, the church has to serve as the foundation of religious harmony. The mindset of Christ in question is the act of Christ who does not defend his rights, the act of Christ who willingly becomes the same as an ordinary man and the act of Christ who takes the form of a slave and acts like a slave who cares for the interests of his master. This study utilizes technical data analysis with a descriptive-interpretive model, which is to elaborate the focus of the study by parsing and re-interpreting it in a certain context. In this case the text described is Philippians 2: 5 using the hermeneutic method as a scalpel and then interpreted in the context of religious harmony in Indonesia. Membangun kerukunan umat beragama merupakan tugas dan tanggungjawab seluruh rakyat Indonesia. Gereja merupakan salah satu bagian dari masyarakat Indonesia yang juga berkewajiban untuk berkontribusi mewujudkan kerukunan umat beragama. Menjawab pertanyaan bagaimana gereja harus bersikap dan bertindak di tengah lingkup masyarakat yang majemuk adalah dengan menawarkan konsep pengajaran mengenai mindset Kristus yang terkandung dalam surat Filipi 2:5 untuk dijadikan sebagai landasan gereja membangun kerukunan umat beragama. Mindset Kristus yang dimaksud adalah tindakan Kristus yang tidak mempertahankan haknya, tindakan Kristus yang dengan rela menjadi sama dengan manusia dan tindakan Kristus yang mengambil rupa hamba dan berlaku seperti hamba yang mementingkan kepentingan tuannya. Penelitian ini menggunakan teknis analisis data dengan model deskripitf-interpretatif yaitu mengelaborasi fokus penelitian dengan cara mengurai dan memaknai kembali pada konteks tertentu. Dalam hal ini teks yang diurai adalah surat Filipi 2:5 menggunakan metode hermeneutik sebagai pisau bedah lalu dimaknai pada konteks kerukunan umat beragama di Indonesia.